2017
DOI: 10.1186/s40510-017-0187-8
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial height in relation to cross-sectional maxillary and mandibular morphology

Abstract: BackgroundIn order to gain a better understanding of how growth of the alveolar bone is linked to the vertical development of the face, the purpose of this study was to investigate if there is an association between the cross-sectional morphology of the maxillary and mandibular bodies with the craniofacial height, using images from cone beam computed tomography (CBCT).MethodsFrom 450 pre-treatment CBCT scans, 180 were selected to be included in the study. Lateral head images were generated from the CBCT scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
5
14
0
2
Order By: Relevance
“…The association between craniofacial height and cross-sectional maxillary and mandibular bone height was most evident in the premolar and incisal regions. These results strengthen the findings of our previous study [16] and are to a certain extent in concordance with the results of the study by Sadek et al [15] where statistical differences were found in the anterior part of the maxilla. Therefore, it can be concluded that the dentoalveolar compensatory mechanism, via continued tooth eruption, responds in the maxilla and mandible by enlarging the vertical size of the frontal dentoalveolar heights in long-face subjects and, conversely, less tooth eruption will take place in short-face subjects [22].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The association between craniofacial height and cross-sectional maxillary and mandibular bone height was most evident in the premolar and incisal regions. These results strengthen the findings of our previous study [16] and are to a certain extent in concordance with the results of the study by Sadek et al [15] where statistical differences were found in the anterior part of the maxilla. Therefore, it can be concluded that the dentoalveolar compensatory mechanism, via continued tooth eruption, responds in the maxilla and mandible by enlarging the vertical size of the frontal dentoalveolar heights in long-face subjects and, conversely, less tooth eruption will take place in short-face subjects [22].…”
Section: Discussionsupporting
confidence: 93%
“…Gracco and co-workers used cone beam CT (CBCT) images of patients to investigate associations between the morphology of the upper jaw, the position of the upper incisors, and craniofacial type as well as the association between the morphology of the mandibular symphysis and the various craniofacial types [13,14]. Also, based on measurements in CBCT images, significant relationships have been found between craniofacial height and alveolar bone height and width in different tooth-bearing regions of the maxilla and mandible [15,16]. With regard to measurements of alveolar bone height and width and the association to craniofacial height, some studies present intrarater agreement [11,15].…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandible was reoriented in order that mandibular plane was parallel to the horizontal (Fig. 1 a) [ 2 , 23 ]. Then mandibular cross-sections between central incisors, lateral incisor and canine, first and second premolars, first and second molars from left and right sides were obtained and saved as JPEG files (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that high-angle group presented thinner alveolus anteriorly in the maxilla and at almost all sites in the mandible. Similarly, Kuitert et al (2006) found that the cortical bone height was statistically significant longer in hyperdivergent faces than hypodivergent ones because of the increased dento-alveolar compensation mechanism occured in long-face patients ( Klinge et al, 2017 ).…”
Section: Discussionmentioning
confidence: 97%